2019
DOI: 10.15252/msb.20188438
|View full text |Cite
|
Sign up to set email alerts
|

Complex‐centric proteome profiling by SECSWATHMS

Abstract: Proteins are major effectors and regulators of biological processes that can elicit multiple functions depending on their interaction with other proteins. The organization of proteins into macromolecular complexes and their quantitative distribution across these complexes is, therefore, of great biological and clinical significance. In this paper, we describe an integrated experimental and computational technique to quantify hundreds of protein complexes in a single operation. The method consists of size exclu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
114
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(124 citation statements)
references
References 62 publications
(123 reference statements)
2
114
0
Order By: Relevance
“…Ribosomes (the major components aggregating in the present study) are especially sensitive to this, as shown by a recent study in turquoise killifish, where ribosomal subunits were enriched in aggregates from aged brains (Sacramento et al 2019). Recent advances in global protein complex profiling techniques (e.g., size exclusion chromatography [SEC]-sequential window acquisition of all theoretical mass spectra [SWATH]-MS) (Heusel et al 2019) will undoubtedly prove fruitful for characterizing protein stoichiometry changes under such conditions. In a similar vein, centrifugation or gel filtration-based proteomics (Geladaki et al 2019) could be used to address whether proteins resident in certain subcellular compartments are especially prone to aggregation.…”
mentioning
confidence: 78%
“…Ribosomes (the major components aggregating in the present study) are especially sensitive to this, as shown by a recent study in turquoise killifish, where ribosomal subunits were enriched in aggregates from aged brains (Sacramento et al 2019). Recent advances in global protein complex profiling techniques (e.g., size exclusion chromatography [SEC]-sequential window acquisition of all theoretical mass spectra [SWATH]-MS) (Heusel et al 2019) will undoubtedly prove fruitful for characterizing protein stoichiometry changes under such conditions. In a similar vein, centrifugation or gel filtration-based proteomics (Geladaki et al 2019) could be used to address whether proteins resident in certain subcellular compartments are especially prone to aggregation.…”
mentioning
confidence: 78%
“…There are many excellent bioinformatics methods developed for proteomics data, including the techniques for normalization and preprocessing (e.g. spectral counts modeling with edgeR [70], MetaMass [71], reviewed in [72]), detecting and quantifying protein complexes (CCprofiler [73]), protein-protein interaction networks analysis and visualization (Cytoscape [74]) as well as dedicated software platforms with a set of statistical tools for high-dimensional proteomics data analysis (e.g. Perseus [75]).…”
Section: Discussionmentioning
confidence: 99%
“…A third method uses a semi-supervised support vector machine classification to determine protein complexes, taking as input co-fractionation data and additional information, such as published PPI datasets, co-evolution based on the assumption that true protein complexes will have conserved sequence and function, and other metrics that describe protein complexes [103]. A third example, CCprofiler [104], introduces a novel 'complex centric' analysis, which is the first to control error rates for protein complex analysis by using a statistical target-decoy method and also makes use of SWATH acquisition (discussed above) to improve the quantitative accuracy of SEC-MS.…”
Section: Size-exclusion Chromatographymentioning
confidence: 99%